2019
DOI: 10.1002/iub.2096
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum long noncoding RNA NEAT and MiR‐129‐5p in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most prevalent form of cancer. Various long non coding RNA (lncRNAs) and micro RNA have been confirmed to have a role in the progression of HCC. Our aim was to investigate for the first time the expression profile of serum level of LNC NEAT (nuclear enrich abundant transcript) and MiR‐129‐5p in HCC patients and their relations with patient's clinical and biochemical investigations rather than previous studies on tissue cell lines. Our study includes 72 subjects divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 29 publications
4
23
0
Order By: Relevance
“…The overlap between the predicted microRNAs and microRNA array results found that miR-129-5p was linked with both LINC00314 and GRM5. Previous studies showed that miR-129-5p function as oncogenes or tumor suppressors during the occurrence and development of multiple cancers, including retinoblastoma [13], non-small cell lung cancer [25], and hepatocellular carcinoma [26]. Its functional role in osteogenic differentiation of ADSCs is poorly demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…The overlap between the predicted microRNAs and microRNA array results found that miR-129-5p was linked with both LINC00314 and GRM5. Previous studies showed that miR-129-5p function as oncogenes or tumor suppressors during the occurrence and development of multiple cancers, including retinoblastoma [13], non-small cell lung cancer [25], and hepatocellular carcinoma [26]. Its functional role in osteogenic differentiation of ADSCs is poorly demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…In a Chinese population study, NEAT1 level was increased in HCC tissues, and served as an independent risk factor for prognosis of HCC [240]. Moreover, the serum level of NEAT1 is also significantly elevated in HCC patients [241].…”
Section: Lncrnas In Hepatocellular Carcinoma (Hcc)mentioning
confidence: 99%
“…69 patients, and there was also a negative correlation between serum NEAT1 and miR-129-5p. 72 Wang et al found that NEAT1 intensified the proliferation and invasion of HCC cells by repressing miR-613, a known tumour driver, by inhibiting DLCK1. 73 In the case of miR-139-5p, researchers revealed that NEAT1 downregulation limited the development of HCC by regulating the miR-139-5p/TGF-β1 axis in vitro and in vivo.…”
Section: Hccmentioning
confidence: 99%